(untitled) (The Batuk, 2025)
This study examines the politics of power and practices embedded in Nepal’s post-1990 development, employing a postmodern framework and Critical Discourse Analysis (CDA). The discourse adopts a postmodern perspective to critique mainstream development practices. The paper critically analyzes the modernity perspective of development through emic and etic lenses, drawing on Derrida’s deconstruction, Escobar’s development critique, Ziai’s, Lyotard’s, and Sapkota’s contributions, and Foucault’s discourse theory. It portrays how the identity of Nepal is being reshaped by MDGs/SDGs, foreign aid, and NGOs, marginalizing the indigenous knowledge and practices thereby promoting mainstream development agenda. It highlights the development discourses, practices that institutions promote particular subjects, realities, and hierarchies, leaving out local voices and practices. Drawing on Gramsci’s theory of hegemony, the paper demonstrates how the local and global elites naturalize the market-driven paradigm to secure social control. The study concludes with a note where equitable development is advocated to represent, magnify, and nurture the various cultural, social, and ecological diversities of Nepal.